GLOBAL CRISIS AND THE ETHICS OF SOLIDARITY - Rošker, Jana (Anali PAZU HD, 2022)
Global crises such as the coronavirus pandemic, which causes a potentially fatal viral disease Covid-19, can never be seen as a one-dimensional or unambiguous problem that could only be solved through medical, biological, or immunological measures. For effective containment of large-scale epidemics, social ethics is also of paramount importance, not only in terms of the problems posed by various decisions regarding triage and similar dilemmas, but simply due to the fact that various ethical systems are part of the historically established models of interpersonal interactions in any human community. In the processes aimed at containing epidemics, we must also take into account the particular degree of incorporated values of interpersonal solidarity and cooperation that prevail in different societies and cultures. Ethical models that prevail in different societies are historically and culturally conditioned. Therefore, transcultural studies can provide us with valuable insights into the internal structure of different types of such models. As an example of such a model, this paper critically presents and analyses the model of traditional Confucian relational ethics (or role ethics), which can serve us as one of the possible bases for creating new strategies against the current and possible future pandemics.